A Comparison of the Bow‐Tie and STAMP Approaches to Reduce the Risk of Surgical Instrument Retention. Issue 5 (6th November 2017) - Chatzimichailidou, Maria Mikela; Ward, James; Horberry, Tim; Clarkson, P. John
Abstract: Although relatively rare, surgical instrument retention inside a patient following central venous catheterization still presents a significant risk. The research presented here compared two approaches to help reduce retention risk: Bow‐Tie Analysis and Systems‐Theoretic Accident Model and Processes. Each method was undertaken separately and then the results of the two approaches were compared and combined. Both approaches produced beneficial results that added to existing domain knowledge, and a combination of the two methods was found to be beneficial. For example, the Bow‐Tie Analysis gave an overview of which activities keep controls working and who is responsible for each control, and the Systems‐Theoretic Accident Model and Processes revealed the safety constraints that were not enforced by the supervisor of the controlled process. Such two‐way feedback between both methods is potentially helpful for improving patient safety. Further methodology ideas to minimize surgical instrument retention risks are also described.